2006
DOI: 10.1159/000091182
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial with Cisplatin-Paclitaxel Cytotoxic Treatment and Concurrent External and Endocavitary Radiation Therapy in Locally Advanced or Recurrent Cervical Cancer

Abstract: Background: Five randomized studies have demonstrated a beneficial effect of adding cisplatin-based chemotherapy to radiation therapy in the treatment of cervical carcinoma. In the present phase II study, we evaluated the response and toxicity of ciplatin-Taxol chemotherapy combined with concomitant radiotherapy in patients with locally advanced cervical carcinoma (LACC) and locally recurrent cervical carcinoma (LRCC). Patients and Methods: In 2000, this phase II study was initiated with a chemotherapy regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…The median RT time in our study was 62 d, similar to the 63-d median reported by Miglietta et al [8]. Adverse effects in our trial were generally tolerable and mild.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The median RT time in our study was 62 d, similar to the 63-d median reported by Miglietta et al [8]. Adverse effects in our trial were generally tolerable and mild.…”
Section: Discussionsupporting
confidence: 89%
“…Due to additional cycle of neoadjuvant chemotherapy before CCRT, Miglieta et al observed full complete clinical response rate and maintained local control [8]. It was assumed that high dose of PTX (175 mg/m 2 every 3 weeks for four cycles) in chemotherapy regimen would contribute to favourable tumor regression in that study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…every 3 weeks for four cycles, 25% and 16% patients display grade 3 or 4 leukopenia and grade 3 or 4 neutropenia, respectively. 12 The reason why our study shows a higher frequency of leukopenia and neutropenia might be explained by a dosage effect, i.e., 4 cycles of paclitaxel (135 mg/m 2 ) combined with cisplatin and radiation in this study might be too much for Asian women. This is in accordance with a Japanese study which reported that the grades of hematological toxicity are significantly greater in weekly cisplatin treatment groups at 40 mg/m 2 (conventional dose in chemoradiation) than at 30 mg/m 2 .…”
Section: Discussionmentioning
confidence: 67%
“…10 Recently, several studies which used cisplatin plus paclitaxel with concurrent radiation have been reported. 9,[11][12][13] These were phase I and/or II studies which focused on evaluating toxicities and response rates in a limited number of enrolled patients. These studies have demonstrated that cisplatin plus paclitaxel concurrently used with radiation show encouraging response rate and good tolerability.…”
Section: Introductionmentioning
confidence: 99%